Gottschall's Problem. - Narechania, Apurva (Common Review)
This article analyzes the dying position of the study of English literature in higher education in the U.S. It reflects on the experience of Jonathan Gottschall in teaching English literature at Washington and Jefferson University in Pennsylvania. It observes that college students in the country have no interest in English literature. The article attributes the dying position of the study to the growth of popular culture and the rising interest in physical fitness.